2017
DOI: 10.1186/s12939-017-0603-1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of intra-household food allocation between adults in South Asia – a systematic review

Abstract: BackgroundNutrition interventions, often delivered at the household level, could increase their efficiency by channelling resources towards pregnant or lactating women, instead of leaving resources to be disproportionately allocated to traditionally favoured men. However, understanding of how to design targeted nutrition programs is limited by a lack of understanding of the factors affecting the intra-household allocation of food.MethodsWe systematically reviewed literature on the factors affecting the allocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
140
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(147 citation statements)
references
References 53 publications
5
140
2
Order By: Relevance
“…141 This is supported by a review of intrahousehold food allocation that shows that inequities are more likely in food insecure or poor households, although this also depends on other factors such as religion, household size, social status, and women's bargaining power. 142 For instance, a study in the far west corner of Nepal showed that adolescent girls ended up second last, or last in case of daughters-in-law, in the household serving order, which could have influenced their nutritional status, especially in food insecure households. 143 Unequal treatment may thus result when households face extreme circumstances, leading to discrimination against vulnerable women.…”
Section: Age and Sexmentioning
confidence: 99%
“…141 This is supported by a review of intrahousehold food allocation that shows that inequities are more likely in food insecure or poor households, although this also depends on other factors such as religion, household size, social status, and women's bargaining power. 142 For instance, a study in the far west corner of Nepal showed that adolescent girls ended up second last, or last in case of daughters-in-law, in the household serving order, which could have influenced their nutritional status, especially in food insecure households. 143 Unequal treatment may thus result when households face extreme circumstances, leading to discrimination against vulnerable women.…”
Section: Age and Sexmentioning
confidence: 99%
“…The intra-household food allocation is determined by social, cultural and environmental factors, especially in the south Asian country like India (Gittelsohn, 2003;Harris-Fry, 2017). Women are often considered of low social status in comparison to men and therefore, they are usually allocated less food and/or less preferred foods (Harris-Fry, 2017).…”
Section: Educationmentioning
confidence: 99%
“…The greater odds of high USFB consumption among female children and lower odds among children from upper caste households has not been reported elsewhere; these results indicate that sociocultural beliefs may be influencing diets of young children in Nepal. Although inequitable intra‐household food allocation by sex has been noted in South Asian contexts including Nepal, (Harris‐Fry, Shrestha, Costello, & Saville, ), literature on the influence of child sex and feeding of USFB is extremely limited. Fledderjohann et al () found greater consumption of fresh milk by sons as compared with daughters among Indian children below 5 years of age; further exploration of our data showed that male children consumed a higher %TEI‐NBF from healthy snacks than female children, particularly dairy‐based snacks.…”
Section: Discussionmentioning
confidence: 99%
“…Ordinal logistic regression model for high consumption a of unhealthy snack foods and beverages (comparison with low/moderate consumption b ) CI: confidence interval.The greater odds of high USFB consumption among female children and lower odds among children from upper caste households has not been reported elsewhere; these results indicate that sociocultural beliefs may be influencing diets of young children in Nepal.Although inequitable intra-household food allocation by sex has been noted in South Asian contexts including Nepal,(Harris-Fry, Shrestha, Costello, & Saville, 2017), literature on the influence of child sex and feeding of USFB is extremely limited Fledderjohann et al (2014). …”
mentioning
confidence: 99%